2016
DOI: 10.3892/mco.2016.940
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia as a prognostic factor and safety of second-line therapy with S-1 for advanced or recurrent pancreatic cancer

Abstract: Abstract. The aim of this retrospective study was to investigate the safety of S-1 as second-line therapy and to evaluate the association between neutropenia occurring during first-line gemcitabine (GEM) therapy and survival for advanced or recurrent pancreatic cancer (APC). Between January, 2010 and December, 2014, 123 APC patients received chemotherapy at the Ogaki Municipal Hospital (Ogaki, Japan). Of those, 37 received GEM as first-line and S-1 as a second-line therapy (GEM→S-1 group). A further 60 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…With regards to cabazitaxel, a post‐hoc analysis of the TROPIC study showed an improvement in OS (16.3 months vs 14.0, HR 0.65, P = 0.035) and PFS (4.6 m vs 2.1 m, HR 0.56, P = 0.001) for patients with Grade ≥3 neutropenia compared to those with Grade <3 neutropenia . A similar association between lack of chemotherapy‐induced neutropenia and worse survival has been shown for many cancers such as Hodgkin's lymphoma, ovarian cancer, non‐small cell lung cancer, breast, gastric, pancreatic, colorectal, and testicular cancers …”
Section: Cytotoxic Agentsmentioning
confidence: 62%
See 1 more Smart Citation
“…With regards to cabazitaxel, a post‐hoc analysis of the TROPIC study showed an improvement in OS (16.3 months vs 14.0, HR 0.65, P = 0.035) and PFS (4.6 m vs 2.1 m, HR 0.56, P = 0.001) for patients with Grade ≥3 neutropenia compared to those with Grade <3 neutropenia . A similar association between lack of chemotherapy‐induced neutropenia and worse survival has been shown for many cancers such as Hodgkin's lymphoma, ovarian cancer, non‐small cell lung cancer, breast, gastric, pancreatic, colorectal, and testicular cancers …”
Section: Cytotoxic Agentsmentioning
confidence: 62%
“…20 A similar association between lack of chemotherapy-induced neutropenia and worse survival has been shown for many cancers such as Hodgkin's lymphoma, ovarian cancer, non-small cell lung cancer, breast, gastric, pancreatic, colorectal, and testicular cancers. [21][22][23][24][25][26][27][28][29][30][31][32][33] The FIRSTANA and PROSELICA trials showed no difference in survival and progression-free survival between 25 and 20 mg/m 2 dosing for cabazitaxel though the toxicity profile was better with 20 mg/m 2 . 34,35 Thus, for a population of patients, a starting dose of 20 mg/m 2 can be recommended for cabazitaxel.…”
Section: Initial Dose Calculationmentioning
confidence: 99%
“…SN is associated with the long-term prognosis of patients with various types of cancer, including breast [ 31 , 32 ], small cell lung [ 33 , 34 ], gastric [ 35 ], colorectal [ 36 , 37 ], ovarian [ 38 ], and pancreatic [ 39 , 40 ]. The long-term prognosis may be associated with SN and CI max , though this was not evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the nature of a cocktail formulation, each component in S-1 exhibits independent PK profile, respectively. Especially the higher C max level of 5-FU derived from tegafur in the blood resulted in hematological and/or GI toxicities in patients for a long-term use 15,20. Accordingly, it is desired to have 5-FU level in blood maintained for a long-time at a relatively low C max level for a new oral candidate of fluoropyrimidine derivatives.…”
Section: Discussionmentioning
confidence: 99%